Sedation scoring and managing abilities of intensive care nurses post educational intervention. Issue 3 (24th April 2015) - Ramoo, Vimala; Abdullah, Khatijah Lim; Tan, Patrick SK; Wong, Li Ping; Chua, Yan Piaw; Tang, Li Yoong
ABSTRACT: Background: Inappropriate sedation assessment can jeopardize patient comfort and safety. Therefore, nurses' abilities in assessing and managing sedation are vital for effective care of mechanically ventilated patients. Aims and objectives: This study assessed nurses' sedation scoring and management abilities as primary outcomes following educational interventions. Nurses' perceived self‐confidence and barriers to effective sedation management were assessed as secondary outcomes. Design: A post‐test‐only quasi‐experimental design was used. Data were collected at 3 and 9 months post‐intervention. Methods: A total of 66 nurses from a 14‐bed intensive care unit of a Malaysian teaching hospital participated. The educational interventions included theoretical sessions, hands‐on sedation assessment practice using the Richmond Agitation Sedation Scale, and a brief sedation assessment tool. Nurses' sedation scoring and management abilities and perceived self‐confidence level were assessed at both time points using self‐administered questionnaires with case scenarios. Sedation assessment and management barriers were assessed once at 9 months post‐intervention. Results: Median scores for overall accurate sedation scoring (9 months: 4·00; 3 months: 2·00, p  = 0·0001) and overall sedation management (9 months: 14·0; 3 months: 7·0, p  = 0·0001) were significantly higher at 9 months compared to 3 months post‐intervention. There were no significant differences in the perceived self‐confidence level for rating sedation level. Overall perceived barrier scores were low ( M  = 27·78, SD = 6·26, possible range = 11·0–55·0). Patient conditions ( M  = 3·68, SD = 1·13) and nurses' workload ( M  = 3·54, SD = 0·95) were the greatest barriers to effective sedation assessment and management. Demographic variables did not affect sedation scoring or management abilities. Conclusions: Positive changes in nurses' sedation assessment and management abilities were observed, indicating that adequate hands‐on clinical practice following educational interventions can improve nurses' knowledge and skills. Relevance to clinical practice: Educational initiatives are necessary to improve ICU practice, particularly in ICUs with inexperienced nurses.